Struktura poezije Svetlane Makarovič med grotesko in metafiziko - Troha, Gašper (Jezik in slovstvo, 2011)
The article analyses the poems Zvezda and Igla by Svetlana Makarovič, which were first published in the collection Tisti čas (1993), and later included bythe author at the end of her selection entitled Samost, which was self-published in 2002. In these two poems, Makarovič clearly shows the form of the modernised ballad, as has been discussed in detail by Boris A. Novak, while at the same time introducing the symbol of the star above the mountain. In addition to a detailed reading of both poems and an analysis of the juxtaposition and counterposition of the sound and sense of the words, the star above the mountain shows itself to be the introduction of a new metaphysics that is no longer able to be enforced and validated through violence, a metaphysics into which is sunk the poet's world. Alongside the thematic and formal approaches, it is above all possible to find parallels between this poetry and in-yer-face theatre, which demonstrates the integration of Svetlana Makarovič's opus in world literary classics.
Keywords: Makarovič, Svetlana, 1939-; Slovenian poetry; Poezija; ballad; in-yer-face theatre; Literarne študije; Kane, Sarah, 1971-1999; Primerjalne študije; slovenska poezija; balada; groteska; gledališče "u fris"; grotesque